2023
DOI: 10.3390/foods12173161
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Protein Fiber Spinning to Develop Plant-Based Meat Analogs via Rheological and Physicochemical Analyses

Kartik Joshi,
Elnaz Shabani,
S. M. Fijul Kabir
et al.

Abstract: The substitution of meat products in the human diet with plant-based analogs is growing due to environmental, ethical, and health reasons. In this study, the potential of fiber-spinning technology was explored to spin protein fiber mimicking the structural element of meat muscle for the purpose of developing plant-based meat analogs. Overall, this approach involved extruding fine fibers and then assembling them into hierarchical fibrous structures resembling those found in whole muscle meat products. Consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In the study of , citrus peel pectin was used to mix with potato to prepare plant-based meat analogs, and the results revealed that the addition of pectin decreased the gel strength of meat analogs and significantly enhanced the gel malleability, and a more porous and fibrous microstructure of this plant-based meat was also observed. Joshi et al (2023) used the fiber-spinning technology to develop plant-based meat prepared by soy protein fiber combined with several PNPs (pectin, xanthan gum, or carrageenan). It was found that these PNPs greatly increased fibers' cohesiveness and created a more porous structure, which provides a new approach for the largescale production of plant-based meat analogs.…”
Section: Plant-based Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of , citrus peel pectin was used to mix with potato to prepare plant-based meat analogs, and the results revealed that the addition of pectin decreased the gel strength of meat analogs and significantly enhanced the gel malleability, and a more porous and fibrous microstructure of this plant-based meat was also observed. Joshi et al (2023) used the fiber-spinning technology to develop plant-based meat prepared by soy protein fiber combined with several PNPs (pectin, xanthan gum, or carrageenan). It was found that these PNPs greatly increased fibers' cohesiveness and created a more porous structure, which provides a new approach for the largescale production of plant-based meat analogs.…”
Section: Plant-based Meatmentioning
confidence: 99%
“…Joshi et al. (2023) used the fiber‐spinning technology to develop plant‐based meat prepared by soy protein fiber combined with several PNPs (pectin, xanthan gum, or carrageenan). It was found that these PNPs greatly increased fibers’ cohesiveness and created a more porous structure, which provides a new approach for the large‐scale production of plant‐based meat analogs.…”
Section: Applications Of Pnps In Typical Future Foodsmentioning
confidence: 99%